2011
DOI: 10.1155/2011/403260
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Airway Diseases by NMR‐Based Metabonomics: A Review of Application to Exhaled Breath Condensate

Abstract: There is increasing evidence that biomarkers of exhaled gases or exhaled breath condensate (EBC) may help in detecting abnormalities in respiratory diseases mirroring increased, oxidative stress, airways inflammation and endothelial dysfunction. Beside the traditional techniques to investigate biomarker profiles, “omics” sciences have raised interest in the clinical field as potentially improving disease phenotyping. In particular, metabonomics appears to be an important tool to gain qualitative and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Proposed and studied biomarker candidates in EBC include pH, cytokines, leukotrienes, nitrogen oxides and organic nitro-compounds, hydrogen peroxide, aldehydes, adenosine, and metabolites. For biomarker discovery, metabolomics and proteomics have been used in both MS and nuclear magnetic resonance applications (5,6 ).…”
Section: Exhaled Breath Condensatementioning
confidence: 99%
“…Proposed and studied biomarker candidates in EBC include pH, cytokines, leukotrienes, nitrogen oxides and organic nitro-compounds, hydrogen peroxide, aldehydes, adenosine, and metabolites. For biomarker discovery, metabolomics and proteomics have been used in both MS and nuclear magnetic resonance applications (5,6 ).…”
Section: Exhaled Breath Condensatementioning
confidence: 99%
“…[2][3][4] Metabolomics studies, which seek to characterize the full range of metabolites within biologic samples, suggest that CF is associated with signifi cant changes in the pattern and concentrations of metabolites in airway secretions, including elevated concentrations of amino acids and lactate in BAL fl uid (BALF) 5 and lipid mediators in sputum. 6 Other studies have demonstrated that a metabolomic signal of CF airways disease can be detected noninvasively in exhaled breath condensate (EBC), 7,8 although the specifi c metabolites responsible for the signal were not identifi ed. Although these studies can provide new insights into pathophysiologic mechanisms and can identify new therapeutic targets and biomarkers of disease progression, 9,10 studies to date are limited by a lack of independent validation to verify results.…”
Section: [ 1 4 8 # 2 C H E S T a U G U S T 2 0 1 5 ]mentioning
confidence: 99%
“…Metabolomics is a useful tool to investigate airways diseases, as the respiratory tract offers a natural matrix (exhaled breath), which is easily collected as exhaled breath condensate (EBC), and contains several biomarkers of [7]. EBC is collected by cooling the exhaled breath, obtaining a liquid that contains evaporated and condensed particles derived directly from the airway lining fluid [8].…”
Section: Application Of Metabolomics To Exhaled Breath Condensatementioning
confidence: 99%